2021
DOI: 10.4103/idoj.idoj_378_20
|View full text |Cite
|
Sign up to set email alerts
|

A Clinico-Epidemiological Study of Cutaneous Leishmaniasis in a Non-Endemic Region of South Rajasthan

Abstract: Introduction: Cutaneous leishmaniasis (CL) is a vector-borne protozoal infection of the skin with variable clinical manifestations. In Rajasthan, western Thar desert is endemic for this disease. Aim: The present study was aimed to describe clinico-epidemiological features of cutaneous leishmaniasis cases from a non-endemic area of South Rajasthan. Materials and Methods: A hospital-based prospective study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 22 publications
3
5
0
Order By: Relevance
“…o of 0.70:1. This is consistent with earlier studies done by Sharma NL et al 7 , Yemisen M et al 8 , Gurel MS et al 9 and Virath R et al 13 In contrast, higher incidence of CL was found in males. 3,6,[10][11][12]14 In Nepal, males are mostly indulged to outdoor works and females to household works.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…o of 0.70:1. This is consistent with earlier studies done by Sharma NL et al 7 , Yemisen M et al 8 , Gurel MS et al 9 and Virath R et al 13 In contrast, higher incidence of CL was found in males. 3,6,[10][11][12]14 In Nepal, males are mostly indulged to outdoor works and females to household works.…”
Section: Discussionsupporting
confidence: 92%
“…The single lesion of CL was mostly seen in 73.91% of the cases in our study, which is consistent with the fi ndings of Pandey K et al 3 , Aara N et al 6 , Sharma NL et al 7 , Yemisen M et al 8 , Gurel MS et al 9 , Gunathilaka N et al 10 , Ghimire PG et al 11 , Galgamuwa LS et al 12 , and Virathet al 13 In contrast, mul" ple lesions were mostly seen in the study by AlSamaraiet al 14 Face was the most common loca" on of single lesion in our study. Similar fi ndings were reported by Pandey K et al 3 , Sharma NL et al 7 , Yemisen M et al 8 , Gurel MS et al 9 , Ghimire PGet al 11 , and Virath R et al 13 In contrast, Aara N et al 6 , Gunathilakaet al 10 , Galgamuwa LS et al 12 , and AlSamarai AM et al 14 reported most common lesions in upper limbs. Lesions presented mainly on exposed parts of the body suggests vectors and sandfl ies could easily access those areas with short sleeved upper clothing items as their vestment and due to the high popula" on density of sandfl ies in those areas.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations